The relationship of retinopathy of prematurity with brain-derivated neurotrophic factor, vascular endotelial growth factor-A, endothelial PAD domain protein 1 and nitric oxide synthase 3 gene polymorphisms. (2nd November 2021) - Ilguy, Serdar; Cilingir, Oguz; Bilgec, Mustafa Deger; Ozalp, Onur; Erzurumluoglu Gokalp, Ebru; Arslan, Serap; Tekin, Neslihan; Aydemir, Ozge; Erol, Nazmiye; Colak, Ertugrul; Gursoy, Huseyin
ABSTRACT: Background: In addition to risk factors such as low birth weight and uncontrolled oxygen therapy, genetic predisposition is also thought to play a role in the development of retinopathy of prematurity (ROP). In our study, we aimed to analyze single-nucleotide polymorphisms (SNPs) in VEGFA, EPAS1, BDNF and NOS3 genes in infants who develop ROP. Materials and Methods: Seventy-five mild-moderate and 73 severe ROP cases were included in this study. Eleven different SNPs regions that located in VEGFA, EPAS1, BDNF and NOS3 genes were analysed by SnapShot technique and compared between two groups by the multiple logistic regression analysis. Results: Statistically significant results were obtained in 8 of the 11 SNPs. It was observed that the excess of mutant alleles in four ( VEGFA rs2010963 and rs3025039, EPAS1 rs13419896, NOS3 rs2070744) of these regions increased ROP severity and treatment requirement ( p < .001, p < .001, p = .022, p = .004, respectively) while the excess of mutant alleles in the other four regions ( VEGFA rs833061, BDNF rs7929344, EPAS1 rs1867785 and rs1868085) showed that ROP severtiy was milder and eliminated the need for treatment ( p < .001, p = .019, p = .017, p = .017, respectively). Conclusions: Considering the results of our study, it was seen that besides the known environmental and demographic factors in ROP pathogenesis, genetic predisposition also had an effect on the clinic and course of ROP. Polymorphisms of VEGFA rs2010963 and rs3025039, EPAS1 rs13419896, NOS3 rs2070744 were found to be associated with severe ROP. More studies involving different populations cases are needed to confirm these findings and enlighten the etiology of ROP.